Theatre Cultures within Globalising Empires Looking at Early Modern England and Spain - Küpper, Joachim; Pawlita, Leonie (De Gruyter, 2018)
This volume presents the proceedings of the international conference "Theatre Cultures within Globalising Empires: Looking at Early Modern England and Spain", held in 2012 as part of the ERC Advanced Grant Project Early Modern European Drama and the Cultural Net (DramaNet). Implementing the concept of culture as a virtual network, it investigates Early modern European drama and its global dissemination. The 12 articles of the volume - all written by experts in the field teaching in the United Kingdom, the USA, Russia, Switzerland, India and Germany - focus on a selection of English and Spanish dramas from the sixteenth and seventeenth centuries. Analysing and comparing motifs, formal parameters as well as plot structures, they discuss the commonalities and differences of Early modern drama in England and Spain.